Measuring Group Dynamics: An Exploratory Trial - Phan, Loan T.; Rivera, Edil Torres; Volker, Martin A.; Garrett, Michael T. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article reports on the development of a scale used to assess and measure group dynamics during group supervision counselling courses (practicum and internship). A 20-item Likert-type scale was administered to 200 counsellors-in-training master’s students. Reliability and validity data are described. An exploratory factor analysis yielded three factors that accounted for 64.4% of the variance. The results of the study support the assessment of group dynamics using the Group Dynamics Inventory. Additionally, the study suggests the possible utility of the Group Dynamics Inventory as a teaching tool to help supervisors to monitor the dynamics in courses that involve group supervision in counsellor training settings such as practica, internships, and fieldwork placements.